2009
DOI: 10.1021/ef9006356
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Emissions from a Baseline Engine Operated with Different Injection Systems and Exhaust Gas Recirculation (EGR) Strategies during Transient Sequences

Abstract: This work is focused on the measurement and analysis of biodiesel emissions resulting from two commercial diesel engines derived from the same baseline engine. One of the engines was equipped with a rotary fuel injection pump electronically controlled. Another engine was equipped with a common-rail injection system. Both engines were tuned by the manufacturer with diesel fuel, and each of them was optimized with different exhaust gas recirculation (EGR) strategies. Both engines were tested under several transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Ghosh et al [31] observed that viscosity of biodiesel varies from 3.5 to 5.5(cSt). Similar results were obtained by Ocatvio and Gomej [17] for sunflower oil. They got results by testing various blends of sunflower oil.…”
Section: Ii1 Viscositysupporting
confidence: 90%
See 3 more Smart Citations
“…Ghosh et al [31] observed that viscosity of biodiesel varies from 3.5 to 5.5(cSt). Similar results were obtained by Ocatvio and Gomej [17] for sunflower oil. They got results by testing various blends of sunflower oil.…”
Section: Ii1 Viscositysupporting
confidence: 90%
“…It produces NOX but is completely free of SOX. It produces less amount of hydrocarbons (HC), CO, PM and CO2 [5,16,17,[19][20][21][22][23][24][25][31][32][33][34][35][36][37][38][39][40][41][42].Wang et al [32] concluded that with increase in blending, NOX emissions also increases. Same Conclusion was given by Leila et al [13].On the other hand, a study tells that other emissions like total Hydrocarbon, Smoke Opacity and PM decreases with blending [43].…”
Section: Figure 1 Transesterification Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other cases, different EGR and injection strategies have been compared in order to study the effect of biodiesel fuels on performance and emissions of Diesel light-duty engines [12].…”
Section: Introductionmentioning
confidence: 99%